The Effect of Agile Principles to Improving Patient Care Quality in Riyadh Private Hospitals (The International Journal for Scientific Research, 2024)
This research investigates the impact of Agile principles on improving patient care quality in private hospitals in Riyadh. Agile methodologies, originally developed for software development, emphasize flexibility, collaboration, and iterative progress, which can be beneficial in the healthcare sector. The study aims to assess how these principles can be adapted to enhance patient care, focusing on key metrics such as patient satisfaction, treatment efficiency, and overall care quality. Through a combination of qualitative and quantitative methods, including surveys and interviews with healthcare professionals and patients, the research explores the practical application of Agile frameworks in hospital settings. The findings indicate that Agile principles, when properly implemented, lead to significant improvements in communication among healthcare teams, faster response times to patient needs, and higher levels of patient satisfaction. Moreover, the iterative nature of Agile practices fosters continuous improvement, ensuring that patient care processes are regularly updated and refined. This study concludes that adopting Agile methodologies in Riyadh's private hospitals can play a crucial role in enhancing the quality of patient care. It provides recommendations for healthcare administrators and policymakers on integrating Agile practices to achieve better health outcomes and improve the overall patient experience.